"A Woman Should Still Be a Woman" – A Grounded Theory of the Origins of Sexual Pain and Difficulties with Intercourse. Issue 7 (30th September 2021) - Koops, Thula U.; Briken, Peer
Abstract: The origin of women's sexual pain and difficulties with intercourse is still under-researched. The aim of this study was to examine women's constructions of origins. Twenty-eight participants previously diagnosed with vaginismus or dyspareunia were recruited via patient lists and private practices. Interviews had a semi-structured biographic-narrative format; transcripts were analyzed using Grounded Theory. Participants' narratives were constructed based on two major processes: Negotiating Womanhood and Othering the Body. They were integrated in an explanatory model. Identified processes permeated women's subjective experience and construction of the origin of their sexual difficulties, and were related to societal discourses and women's embodied experience.